Participação do óxido nítrico (NO) na modulação central da hiperalgesia na artrite induzida por zymozan (AZy) em ratos - Girão, Virgínia Cláudia Carneiro (2006)
We investigate in this work the role of the central nervous system in the modulation of the inflammatory peripheral pain in the zymosan induced arthritis (AZy) in rats. Cerebrospinal fluid (CSF) and sinovial fluid were collected from animals at different AZy times (1, 3, 6, 12 and 14 hours) in order to determine the nitrite level. Different groups of male, Wistar rats (n=6), 250 to 300g weight, were then submitted to surgery in order to place a cannula in the subarachnoid space, to allow for intrathecal (i.t) insertion of substances. The animals were also submitted to AZy followed by the paw suspension test (PST) that measures articular incapacitation (AI), aiming to analyze hyperalgesia in this experimental model. The pharmacological modulation was achieved by the prophylactic or therapeutic i.t administration of a NO donor (SIN-1), NOS inhibitors (L-NAME, 1400W), a soluble Guanylate cyclase inhibitor (ODQ), a GMPc analogue (8-Bromo-GMPc) and an NMDA receptor antagonist (MK-801). The ODQ was also administered intraarticulary to one group of animals. The results are expressed as mean ± s.e.m, followed by ANOVA and the Tukey test, comparing to the groups that received the vehicle. The levels of nitrite in the CSF were smaller at 1 and 3 hours after zymosan injection, as compared with basal levels (P<0.05). The surgical procedure did not alter hyperalgesia. SIN-1 i.t (10 mcg) reduced the AI, while 40mcg increased the AI (P<0.05). L-NAME or 1400W, prophylactic or therapeutic, reduced the AI (P<0.05). ODQ i.t, prophylactic, but not therapeutic, reduced the AI, and also reverted the AI promoted by the 40mcg of SIN-1. Besides, ODQ, intraarticulary, reverted the AI promoted by the 40mcg of SIN-1, administered i.t. MK-801 i.t inhibited the AI, both caused by AZy and by the 40mcg of SIN-1. The results suggest a central endogenous anti-nociceptive role of NO in the acute articular hyperalgesia of the AZy. The NO, depending on the dose and local where it acts, may present an anti-nociceptive or pro-nociceptive effect in the AZy, both due to the activation of GMPc and the excitation of NMDA receptors. We have shown, for the first time, the existence of a peripheral-central activation way modulating the articular hyperalgesia in the AZy acute phase.